2018
DOI: 10.1038/s41598-018-34617-y
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and physical activity in middle-aged and older adults in China

Abstract: There are few studies examining the association between levels of physical activity and hypertension in middle-aged and older adults in China. Data were drawn from the Chinese Health and Retirement Longitudinal Study (using four-stage stratified probability-proportional-to-size sampling), involving 7113 individuals aged 45 years and older from 28 provinces of China. Hypertension was defined as a systolic BP ≥ 130 mm Hg, or diastolic BP ≥ 80 mm Hg, or self-reported use of anti-hypertensive medications. The awar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
23
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 24 publications
8
23
1
3
Order By: Relevance
“…Furthermore, overweight and obesity are important risk factors affecting the incidence of hypertension [18]. You et al [19] showed that even 10 min of vigorous physical activity every week can help reduce the prevalence of hypertension. Several studies abroad and in the country have examined the relationship between physical activity and hypertension [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, overweight and obesity are important risk factors affecting the incidence of hypertension [18]. You et al [19] showed that even 10 min of vigorous physical activity every week can help reduce the prevalence of hypertension. Several studies abroad and in the country have examined the relationship between physical activity and hypertension [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The results of randomized controlled trials (RCTs) showed RPA could reduce the blood pressure of patients with hypertension [ 46 ]. The results of the decision tree showed that vigorous physical activity seemed to be more important than moderate and light activity to induce beneficial effects on the prevention of hypertension [ 47 ]. However, in turn, few studies used RPA participation as an outcome variable to analyze the possible effects of PDH on RPA.…”
Section: Discussionmentioning
confidence: 99%
“…Insufficient training can be a barrier to physical exercise, and in regard to people with arterial hypertension, the presence of this factor can hinder nonpharmacological treatment. Studies show the relationship between regular physical exercise and a reduction in blood pressure (Boutcher & Boutcher, 2017;Lavie et al, 2019;You et al, 2018).…”
Section: Related Factorsmentioning
confidence: 99%